GETTING OUT OF THE “VALLEY OF THIS WOEFUL LIFE”: BLACK FEMINIST DISCOURSE IN A MERCY - AZON, Sènakpon Adelphe Fortuné (My University, 2021)
This paper explores, throughA Mercy, Toni Morrison’spreoccupation with the black female condition inthe dawn of the American race-based slavery system, and the construction of a liberating feminist discourse. It revisits the negotiation of the power dynamics in the seventeenth-century America by positing that remembering and re-interpreting the past constitutes a royal way to shed light on the present. The memory of slavery from thefemale’s perspective also helps construct the discourse of black women’s liberation today. Using a black feminist interpretive frame, this research work analyzes, in the novel, the social struggles from the stance of the enslaved female thrown against the other social subjectivities in early America, for an advocacy of black females’condition. It thus purports to contribute to the liberation of black females in contemporary America.
Keywords: Key-words: Black feminism – slavery – liberation – domination – discourse